Hypertrophic Neuropathy Secondary to Hansen's Disease. A Case Report - María Octavina Rodríguez Roque; Didiesdle Herrera Alonso; Ada Sánchez Lozano (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
We present the case 49-year-old unmarried woman treated at the hospital of Cienfuegos. The patient complained of weakness in the lower limbs and "numbness" (paresthesia) of all four extremities, which improved slightly after treatment. A year later, the muscle weakness and paresthesia worsened, particularly in the upper limbs. She also developed hypopigmented skin lesions on the chest and abdomen. The investigation was initiated due to suspicion of hypertrophic polyneuropathy. A biopsy of the hypochromic lesions was performed, which led to the conclusion that the patient suffered from a hypertrophic polyneuropathy secondary to tuberculoid Hansen's disease. We decided to present this case since a neuropathy is usually slow, insidious and has a long course in these patients; however, leprosy reactions can lead to acute nerve damage, resulting in disabilities and deformities. Consequently, it is important to act quickly in order to avoid them.